Phagocytosis Is the Sole Arm of Drosophila melanogaster Known Host Defenses That Provides Some Protection Against Microsporidia Infection - Caravello, Gaëtan; Franchet, Adrien; Niehus, Sebastian; Ferrandon, Dominique (Frontiers in Immunology, 2022)
Microsporidia are obligate intracellular parasites able to infest specifically a large range of species, including insects. The knowledge about the biology of microsporidial infections remains confined to mostly descriptive studies, including molecular approaches such as transcriptomics or proteomics. Thus, functional data to understand insect host defenses are currently lacking. Here, we have undertaken a genetic analysis of known host defenses of the Drosophila melanogaster using an infection model whereby Tubulinosema ratisbonensis spores are directly injected in this insect. We find that phagocytosis does confer some protection in this infection model. In contrast, the systemic immune response, extracellular reactive oxygen species, thioester proteins, xenophagy, and intracellular antiviral response pathways do not appear to be involved in the resistance against this parasite. Unexpectedly, several genes such as PGRP-LE seem to promote this infection. The prophenol oxidases that mediate melanization have different functions; PPO1 presents a phenotype similar to that of PGRP-LE whereas that of PPO2 suggests a function in the resilience to infection. Similarly, eiger and Unpaired3, which encode two cytokines secreted by hemocytes display a resilience phenotype with a strong susceptibility to T. ratisbonensis.